Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1016/j.ejcts.2009.07.038
|View full text |Cite
|
Sign up to set email alerts
|

Rotation thromboelastometry (ROTEM®) stability and reproducibility over time☆

Abstract: ROTEM yields stable results over 120 min with a minimal variability on the same ROTEM device. However, small but significant differences between ROTEM devices were observed. Analysis should be performed on the same ROTEM device if small differences are of importance for treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
101
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 125 publications
(110 citation statements)
references
References 24 publications
6
101
0
3
Order By: Relevance
“…Female patients had higher MA levels than males (66.5 vs. 62.8, p < 0.001), which was consistent with Rafiq et al who reported that more female CABG patients presented with TEG-hypercoagulability and in healthy population female sex and older age are associated with hypercoagulability [6,20,21]. It has frequently been reported that women develop more severe strokes and have worse functional outcomes than men after ischemic stroke [22,23].…”
Section: Discussionsupporting
confidence: 79%
“…Female patients had higher MA levels than males (66.5 vs. 62.8, p < 0.001), which was consistent with Rafiq et al who reported that more female CABG patients presented with TEG-hypercoagulability and in healthy population female sex and older age are associated with hypercoagulability [6,20,21]. It has frequently been reported that women develop more severe strokes and have worse functional outcomes than men after ischemic stroke [22,23].…”
Section: Discussionsupporting
confidence: 79%
“…In this study, the diagnosis of thrombocytopenia and dilutional coagulopathy was possible using the A10, which is supported by recent findings that more than 98% of the final MCF was reached after 10 min runtime in patients scheduled for nonemergent surgery. 42 Furthermore, this also corresponds to clinical observations in noncardiac surgery where A10 was found suitable for fast interpretation of thromboelastometric analysis.# Several study limitations merit attention. The current study was performed on modeled coagulopathies in WB.…”
Section: Discussionmentioning
confidence: 99%
“…With INTEM, coagulation is initiated by contact activator leading to intrinsic pathway activation. The inhibition of the platelets by cytochalasin D in the FIBTEM test shows the fibrinogen clotting which corresponds to fibrinogen plasma levels and can be visualized [16,17]. Furthermore the amount of factor XIII plays a role regarding the maximal amplitude of this test [18].…”
Section: Clot Formation In Whole Blood Thromboelastography and Rotatimentioning
confidence: 99%